2016
DOI: 10.1002/jaba.284
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcer choice as an antecedent versus consequence

Abstract: Four children with autism received opportunities to choose among several preferred stimuli either immediately before or after task responding. The response requirement for reinforcement systematically increased within each session. Two children engaged in higher levels of responding when reinforcement choice was provided as an antecedent to task completion, and 3 of the 4 children showed a preference for the antecedent choice condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 9 publications
2
18
2
Order By: Relevance
“…The antecedent and consequence choice conditions were similarly effective for Olivia. This finding is similar to the results for two participants from Peterson et al (2016), who demonstrated similar patterns of responding during the antecedent and consequence choice conditions. Similar levels of responding across conditions may have occurred because the token exchange schedule was a fixed ratio 3.…”
Section: General Proceduressupporting
confidence: 88%
See 3 more Smart Citations
“…The antecedent and consequence choice conditions were similarly effective for Olivia. This finding is similar to the results for two participants from Peterson et al (2016), who demonstrated similar patterns of responding during the antecedent and consequence choice conditions. Similar levels of responding across conditions may have occurred because the token exchange schedule was a fixed ratio 3.…”
Section: General Proceduressupporting
confidence: 88%
“…Teachers commonly provide choice among reinforcers during instruction for learners with autism spectrum disorder (ASD; Howell, Dounavi, & Storey, 2018;Peterson, Lerman, & Nissen, 2016). Two approaches for doing so are for a teacher to provide a choice of reinforcer prior to (antecedent choice) or following (consequence choice) a response requirement.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hayes and Fryling are more sympathetic to the evocative function of MOs-induction of response classes in the context of an S D that is pertinent to a consequence R C resonating with the organism's state, O. Both classic (Berridge, Robinson, & Aldridge, 2009) and recent (Peterson, Lerman, & Nissen, 2016) research supports this view. In later threads of the strand of behavior, presentation of the reinforcer itself becomes a very important part of the context (e.g., .…”
Section: Selection By Consequencesmentioning
confidence: 97%